The noise silence makes secularity and Ghana's drum wars - Goshadze, Mariam (Durham London Duke University Press, 2025)
"The Noise Silence Makes analyzes the annual, city-wide ban on noise-making required by the Ga indigenous community in Accra in preparation for the Ga's primary religious festival. The centuries-old "ban on drumming" tradition became a point of conflict in the 1990s when newly popular Pentecostal/Charismatic churches refused to subdue their loud worship during the ritual period. The state's response to the "Drum Wars" sheds light on the backstage reality of Ghanaian secularity, wherein the state unofficially collaborates with indigenous religious authorities to control sound in Accra, yet constitutionally and institutionally grants superior status to Christianity and Islam as the country's "religions". Noise regulation technologies used to control the Ga in the colonial context mutated into a mechanism that they now deploy to counter Pentecostal/Charismatic Christianity, revealing the vitality of indigenous religion in urban West Africa. The secular Ghanaian state has found in favor of indigenous religion, ironically by denying "religious" status to indigenous rituals, while "religious" communities, like Pentecostal and evangelical Christians, must defer to the sonic demands of Ga communities. Contrary to the assumption that culturalization of indigenous religions will lead to their marginalization, Mariam Goshadze shows that the culture label lets the Ga remain active in the secular public sphere and is largely responsible for their continuous leverage. The author shows that sound, or its absence, is a powerful means of structuring inter-communal relations. This work offers an important corrective to the implicit hierarchies of religions still present in the study of religion"--
Altered ontologies and reversed paradigms -- Jumping on the anti-noise bandwagon : drumming permits for Accra's residents -- Winds of change : The ban on drumming enters the public sphere -- The power of sound : cross-world sonic theologies -- When the deities visit : translating religion into the language of the secular -- Sacred acoustic inspectors : Ghanaian state and noise abatement during the festival -- Let us offer thanks for the nation of Ghana : as a civil ceremony of thanksgiving -- Layered epistemologies of contemporary Accra.
Includes bibliographical references and index
Keywords: Gã (African people) -- Religion; Gã (African people) -- Rites and ceremonies; Drum -- Performance -- Ghana -- Religious aspects; Noise control -- Law and legislation -- Ghana -- Accra; Christianity and other religions -- Ghana -- Accra; Accra (Ghana) -- Religious life and customs